Preface - A, Dang Quang; Tu Bao, Ho; Dung, Dinh; Ha Duong, Phan; Khoa Son, Nguyen; Duc Thi, Vu (Journal of Computer Science and Cybernetics, 2021)
This Special Issue of Journal of Computer Science and Cybernetics is dedicated to Professor Phan Dinh Dieu on the occasion of his 85th birth anniversary.